Comparing efficacy of octyl-cyanoacrylate dermabond adhesive glue versus vicryl 3/0 suture for closure of caesarean section skin incision in UKMMC- a prospective randomised controlled trial. - Annamalai,; Mohd Nasir Shafiee,; Zuraidah Che' Man,; Nur Azurah Abd Ghani,; Nor Azlin Mohamed Ismail,; Lee, Choon Yee; Lim, Pei Shan; Nirmala Kampan, (Department of Surgery, UKM Medical Centre, 2014)
This is a prospective randomised controlled trial conducted at a tertiary hospital on 82 women who underwent caesarean section. The study group, 41 women underwent dermabond skin closure whereas the control group, 41 women had subcuticular vicryl skin closure. Anaesthesia, prophylactic antibiotic, operative technique and post-operative oral analgesia was standardised between both groups. Outcomes that were measured at day 2 before discharge and at postoperative day 10-14 were pain score using VAS, duration and total analgesic dose (after day 2), time taken for skin closure and adverse events between both groups in particular inflammation, surgical site infection and allergic reaction (itching).